Examining Employment Outcomes of Offender and Nonoffender Vocational Program Graduates - Formon, Dana L. (International journal of offender therapy and comparative criminology, 2018)
Researchers have found providing employment opportunities for ex-offenders through job training programs to be effective at reducing recidivism. Examining various community-based programs for ex-offenders can be beneficial as they may be able to provide more stable and consistent programming without relying on the justice system. This study examined employment outcomes of graduates with and without criminal histories (n = 617) from a community-based vocational training program. Results showed that ex-offender graduates obtained employment at equal rates to nonoffender graduates and received equal pay to their nonoffender counterparts. This could indicate that for the vocationally educated ex-offender, employment outcomes may be able to equal those of other job-searching individuals with similar backgrounds but without a criminal history. Community-based programs for ex-offenders may be able to provide effective programming to improve vocational attainment within this group, thereby potentially easing the burden on criminal justice institutions as the sole provider of offender rehabilitation.